Hubungan Penggunaan Gawai dengan Hipperaktivitas dan Interaksi Sosial pada Anak Usia Sekolah di SD Negeri 2 kalibagor - isnaeni aldina novita rahmah isnaeni aldina novita rahmah (Journal of Bionursing, 2020)
ABSTRACT Background: The use of gadgets can have a significant negative impact on children. Ease of accessing various information and technology makes children lazy to move. In addition, spending too much time in front of the screen interferes with children's social interactions. Hyperactivity behavior of children often makes them have difficulty undergoing interpersonal relationships with parents, peers, and the surrounding environment. Objective: This research aimed to find out the correlation between the use of gadgets with hyperactivity and social interaction on school-age children in SDN 2 Kalibagor. Method: This was a quantitative descriptive study using a cross sectional approach. The research sample was 49 school-age children taken by simple random sampling technique. The measuring instrument used was a questionnaire sheet and chi square test was employed to analyze the data obtained. Results: The majority of respondents were male (59.2%) and aged 11 years (67.3%). 75.5% of the respondents used bad gadgets. 53.1% of them did not experience hyperactivity, while 46.9% of them experienced low interaction. The analysis indicated that p = 0.004 for the use of gadgets with hyperactivity, and the value of p = 0.001 for the use of gadgets with social interactions. Conclusion: There is a correlation between the use of gadgets with hyperactivity and social interaction on school-aged children at SD N 2 Kalibagor. Keywords: Hyperactivity, social interaction, use of gadgets